Summorum Pontificium: The External Form of the Latin Rite Mass - Glendinning, Chad J. (Roman Replies and CLSA Advisory Opinions 2011, 2011)
A newly ordained priest has expressed a desire to celebrate Mass according to the 1962 Missale Romanum in a parish of which he has been appointed pasochial vicar. The pastor of the parish is not agreeable and does not want such Masses publicly celebrated. He claims that the few parishioners who have expressed an interest in the extraordinary form have done so only recently, and that the parochial vicar is simply imposing his own liturgical preferences on the parish. What can be done to resolve this stalemate?